THE REFLECTION OF SOCIAL VALUES IN THE CHARACTER OF FREDERICK WENTWORTH IN JANE AUSTEN’S, PERSUASION - A. Lagonah, Yunia Prasticia; Baga, Magdalena; Usu, Novi Rusnarty (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
This study aimed to describe the reflection of social values using the analysis of Sociology of Literature under the character of Frederick Wentworth in Persuasion by Jane Austen. This study was a qualitative descriptive study using the approach of Sociology of Literature. The data was collected through note-taking method which was primary obtained from the novel of Jane Austen Persuasion. It was then analysed using the sociology of literature by only focusing on the sociology of the work aspect. The results of the study showed that there were discriminations and judgements towards the character of Frederick due to his social status. However, Frederick's character who was dealing with a society that prioritised great importance on social status was not affected by the assessment directed at him. The character of Frederick has reflected the value of social, such as tolerating and dedicating as the opposition of values that he had to receive. Hence, the judgement which emerged had no bad influence at all in the development of his character.